2021
DOI: 10.7759/cureus.20477
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Robotic Partial Nephrectomy Conversion to Radical Nephrectomy: A Retrospective Multi-Institutional Analysis in the Michigan Urologic Surgery Improvement Collaborative (MUSIC)

Abstract: Objective: To identify factors related to the conversion of robot-assisted partial nephrectomy (RPN) to robot-assisted radical nephrectomy (RRN) based on data collected by a statewide database in Michigan. Methods: Using the Michigan Urological Surgery Improvement Collaborative-Kidney mass: Identifying and Defining Necessary Evaluation and therapY (MUSIC-KIDNEY) database we identified 574 patients for whom RPN was planned. Patient and tumor characteristics were obtained including body mass index (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The 4.2% rate of conversion to RN reported in our study is comparable to other rates reported in literature, which have ranged from 0.14% to 14%. [11][12][13][14][15][16] Identifying patients who are at a high risk of conversion to RN may help inform preoperative counseling. Our study identified that patients with larger and high-complexity tumors were more likely to undergo conversion to RN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 4.2% rate of conversion to RN reported in our study is comparable to other rates reported in literature, which have ranged from 0.14% to 14%. [11][12][13][14][15][16] Identifying patients who are at a high risk of conversion to RN may help inform preoperative counseling. Our study identified that patients with larger and high-complexity tumors were more likely to undergo conversion to RN.…”
Section: Discussionmentioning
confidence: 99%
“…score, hilar tumors/renal sinus invasion, laparoscopic PN, intraoperative bleeding, positive surgical margins, and advanced pathological tumor stage. 11,12,14,15 Assessment of tumor complexity is a necessary component to identify tumors at high risk for conversion and other complications. 19,20 Dahlkamp et al demonstrated the value of R.E.N.A.L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, conversions to RN appear to be more common in open surgical approaches with reported incidences of 2.3% to 13.5% compared to 1.2% to 5.9% among cases managed with MI approaches. 8,10,11,13,[17][18][19][20] Nevertheless, conversion comparisons between open and MI PN have yielded conflicting results. In an evaluation of 177 consecutive patients undergoing planned PN, Long et al found the odds of conversion to RN to be 3 times more likely in robotic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Data describing the incidence of, reasons for, and patient and tumor characteristics associated with increased risk of conversions from PN to RN are sparse and often conflicting. [8][9][10][11][12][13] As the adoption of nephron-sparing surgery for localized kidney masses continues to grow and the limits of such approaches are increasingly tested, a better understanding of conversion risk is needed. 14,15 Identifying which patients are at increased risk of conversion to RN is important for identifying the limitations of this management option, guiding operative planning, and improving patient counseling.…”
mentioning
confidence: 99%